THE ANALYSIS OF COGNITIVE DOMAIN IN READING EXERCISES TEXTBOOK FOR GRADE XI SENIOR HIGH SCHOOL - ADE LESTARI DWI PUTRI; ANGGRAINI THESISIA SARAGIH; NORA RONITA DEWI (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
This study aims to find out kinds of cognitive domain based on Revised Bloom’s Taxonomy in reading exercises textbook for grade XI Senior High School and found the distribution of the lower and higher order thinking skill in reading exercises. This study was conducted by using descriptive qualitative method. The data of this research were the reading exercises in the Pathway to English textbook for grade XI Senior High School with 2013 Curriculm published by Erlangga in 2017. After analyzed the data, the result of the study was the reading exercises in the textbook covered all of the cognitive domains, they were remembering level was 37,1 %, understanding level was 50 %,  applying level was 3,37 %, analyzing  level was 1,35 % , evaluating  level was 4 %, and creating  level was 4%. It was concluded that there was inequality number in the distribution of high and low thinking skill in reading exercises in the Pathway to English textbook for grade XI Senior High School and it cannot improve student’s critical thinking.  Keywords: Cognitive domain, Reading exercises, Revised Bloom’s Taxonomy